2022
DOI: 10.1002/mrm.29378
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and correction of diffusion gradient‐induced eddy currents in second‐order motion‐compensated echo‐planar and spiral cardiac DTI

Abstract: Purpose: Very high gradient amplitudes played out over extended time intervals as required for second-order motion-compensated cardiac DTI may violate the assumption of a linear time-invariant gradient system model. The aim of this work was to characterize diffusion gradient-related system nonlinearity and propose a correction approach for echo-planar and spiral spin-echo motion-compensated cardiac DTI. Methods: Diffusion gradient-induced eddy currents of 9 diffusion directions were characterized at b values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…If an oscillatory gradient waveform is used, the output will also reflect the beat phenomenon, given that the GMTF resolves the mechanical resonance. However, given that the LTI assumption may not hold for strong gradients as used in diffusion MRI, 11 the validity of the gradient correction may be limited as well. In addition, the time horizon for the impulse response (and therefore for the validity of the convolution) is limited by the time duration of the GMTF acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If an oscillatory gradient waveform is used, the output will also reflect the beat phenomenon, given that the GMTF resolves the mechanical resonance. However, given that the LTI assumption may not hold for strong gradients as used in diffusion MRI, 11 the validity of the gradient correction may be limited as well. In addition, the time horizon for the impulse response (and therefore for the validity of the convolution) is limited by the time duration of the GMTF acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a GMTF measurement permits, for example, the correction of k-space trajectories of echo planar, 4,5 spiral, [6][7][8][9] or radial imaging 10 sequences. However, the validity of the LTI assumption can be challenged if nonlinearity effects (e.g., due to strong diffusion gradients 11 ) or temperature changes 12 in the gradient chain are no longer negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In the setup used for the current work, due to the nature of the field camera in use, measurements of the field dynamics had to be performed after the actual scanning, thereby effectively doubling the required scan time. This, however, can be tackled readily with cameras designed for concurrent field monitoring 62 or one‐time calibration‐based gradient impulse response modeling 63–65 …”
Section: Discussionmentioning
confidence: 99%
“…This, however, can be tackled readily with cameras designed for concurrent field monitoring 62 or one-time calibration-based gradient impulse response modeling. [63][64][65] The key aim of T-Hex is to minimize the number of shots needed, by maximizing k-space coverage per shot. This is particularly relevant for dMRI with high b-values and long diffusion or mixing times, 66 which incur a large time overhead per shot.…”
Section: F I G U R Ementioning
confidence: 99%
“…This technique holds promise for enhancing our understanding of cardiac diseases and their impact on myocardial microstructure. [1][2][3][4] By measuring key parameters such as the trace apparent diffusion coefficient (trADC), fractional anisotropy (FA), and myofiber orientation, cDTI enables the characterization of healthy and pathological myocardial tissue. Studies in healthy volunteers have demonstrated the effectiveness of cDTI in assessing myocardial microstructure.…”
Section: Introductionmentioning
confidence: 99%